2000
DOI: 10.1046/j.1365-2885.2000.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum concentrations following continuous intravenous infusion of dexmedetomidine or medetomidine in cats and their sedative and analgesic effects

Abstract: Dexmedetomidine (DEX) may have some therapeutic advantages over the racemate medetomidine (MED). Here we have examined how serum concentrations of DEX correlate with some of its anaesthetic effects. Cats (n = 6) were administered with a continuous stepwise intravenous (i.v.) infusion of DEX or MED on different occasions in a cross-over design. Maintenance infusion rates (mg/kg/min) used were: DEX = 0.25 (MED = 0.50); DEX = 1 (MED = 2) and DEX = 4 (MED = 8) for infusion steps 1, 2 and 3, respectively. Each main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 25 publications
7
45
0
3
Order By: Relevance
“…[11][12][13] Additionally, increases in cardiac preload caused by bradycardia or α 2 -agonist-induced venoconstriction, as suggested by an increase in central venous pressure, would be expected to increase cardiac inotropy via the Starling mechanism. 10 Analysis of results of the study reported here and results of other studies 6,9,10,[23][24][25] in dogs, cats, and horses suggests that maximum cardiovascular effects of currently available α 2 -agonists can be reached at clinically relevant dosages and before maximum sedative effects are observed. Similar conclusions have been reached by other investigators who have conducted research on dose-response characteristics of medetomidine in dogs and cats.…”
mentioning
confidence: 64%
“…[11][12][13] Additionally, increases in cardiac preload caused by bradycardia or α 2 -agonist-induced venoconstriction, as suggested by an increase in central venous pressure, would be expected to increase cardiac inotropy via the Starling mechanism. 10 Analysis of results of the study reported here and results of other studies 6,9,10,[23][24][25] in dogs, cats, and horses suggests that maximum cardiovascular effects of currently available α 2 -agonists can be reached at clinically relevant dosages and before maximum sedative effects are observed. Similar conclusions have been reached by other investigators who have conducted research on dose-response characteristics of medetomidine in dogs and cats.…”
mentioning
confidence: 64%
“…However, side effects were observed when DEX is used at high doses. In fact, it is observed that sedation and analgesia induced by DEX, unlike MED, reach a ceiling effect beyond which further dosages decrease sedation level (Schwinn et al 1991;Ansah et al 2000) and that LEV, 50% of MED, also produces signs of sedation or analgesia (Doze et al 1989;Savola and Virtanen 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies in dogs and cats have shown that the pharmacodynamic effects of DEX are twice as potent as the MED racemic mixture, therefore DEX is administered at half the dose of MED for sedation; as for MED, the sedative and analgesic effects of DEX are antagonised by atipamezole (Cullen 1996;Ansah et al 1998Ansah et al , 2000Kuusela et al 2000;Mendes et al 2003;Granholm et al 2006). DEX has been approved for clinical use in dogs and cats in Italy since 2008, and we immediately started to use it for dog and cat sedation.…”
Section: Introductionmentioning
confidence: 99%
“…Levomedetomidine is practically devoid of pharmacological activity (MacDonald et al, 1991;Savola and Virtanen, 1991). In veterinary use for dogs and cats, medetomidine was originally used as a racemic mixture (Ansah et al, 2000;Kuusela et al, 2000), but it was recently launched as a formulation containing only the pure dextroenantiomer.…”
Section: Pression-normalized V Max Values Levomedetomidine [(؊)-4-(rmentioning
confidence: 99%